2017
DOI: 10.2298/sarh151123004i
|View full text |Cite
|
Sign up to set email alerts
|

Impact of reconstructive procedures with and without preserving the duodenal passage on body weight in patients after total gastrectomy for gastric cancer

Abstract: Introduction/Objective The ideal reconstruction procedure after total gastrectomy should replace all lost functions of the stomach. The aim of this study was to evaluate the usefulness of preserving the duodenal passage in subsequent improvement of body weight (BW) and body mass index (BMI) in patients with gastric cancer after total gastrectomy. Methods A total of 30 patients with gastric cancer were prospectively randomly divided into a group of reconstruction with double-tract (n = 15) and a group of recons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 19 publications
1
15
0
1
Order By: Relevance
“…Reasons included: unclarified reconstruction methods, mixed with reconstruction methods other than DT and RY, no outcome of interest, duplications. Finally, 8 studies [8][9][10][11][12][13][14][15] were eligible for the meta-analysis, among which, 2 were RCTs 9,10 and 6 were nonrandomized matched cohort studies. 8,[11][12][13][14][15] A summary of the included studies with the general clinical characteristics and quality assessment is shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Reasons included: unclarified reconstruction methods, mixed with reconstruction methods other than DT and RY, no outcome of interest, duplications. Finally, 8 studies [8][9][10][11][12][13][14][15] were eligible for the meta-analysis, among which, 2 were RCTs 9,10 and 6 were nonrandomized matched cohort studies. 8,[11][12][13][14][15] A summary of the included studies with the general clinical characteristics and quality assessment is shown in Table 1.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Patient age and gender were balanced between Group DT and Group RY in 6 studies. [10][11][12][13][14][15] Four studies [10][11][12][13][14] recorded body mass index (BMI) of both groups, with no significant difference. In all studies, gastrectomy was carried out for gastric carcinoma.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Relative pancreatic insufficiency may also lead to malabsorption of patients in whom reconstruction excludes the passage of food through the duodenum [54]. Studies have shown that patients with TG who have undergone DP prevention have less loss of body weight and body mass index and have fewer symptoms as consequences of RP [55][56][57][58]. Fat and protein malabsorption occurs in over 50% of patients after total gastrectomy.…”
Section: Advantages Of Reconstructive Procedures With Preservation Dumentioning
confidence: 99%